A Comparative Study on Data Mining Applications - Bhardwaj, Brijesh Kumar (International Journal of Computer Sciences and Engineering, 2019)
Data mining is broadly utilized in assorted territories. There is various business data mining framework accessible today but there are numerous difficulties in this field. This paper explains use of new terminology (decision tree) in educational data mining. Decision tree are used the data comparison with data mining capability. It helps prior in distinguishing the dropouts and understudies who require exceptional consideration and enable the educator to give suitable exhorting/advising.